RESTORATIVE JUSTICE SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA KELALAIAN MEDIS - Tisa Windayani; Nugroho Adipradana (Universitas Katolik Indonesia Atma Jaya, 2020)
Medical negligence in Indonesia can be considered as criminal conduct. Though the nature of medical contract—relationship is private, but it is considered to have public aspects. The criminalization of medical negligence is intended to protect citizen from any malpractice by medical workers. While there are enough lawsuits and cases being reported to the police, yet the conclusions are still in the shadow. There are some rules regarding some standards, either it is on the medical treatment procedures, or on the terms and procurements of the medical workers. Interestingly, failing on these standards come along with criminal punishment on. Yet, in some cases, we found out that criminal punishment being ruled out. Instead, the proceeding uses restorative justice. Restorative justice is a state of the art criminal proceeding that weighing on repairing damages on victim, caused by criminal conduct—than to punish the perpetuator. Using theories within the Criminal Study like the “goals of punishment”, justice theories, and restorative justice theories as well; we conclude that the switch of punishment into other obligation for victim’s sake is a good application of restorative justice